2012
DOI: 10.1007/s00234-011-1003-7
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic middle meningeal artery pseudoaneurysms

Abstract: Intracranial pseudoaneurysms are rare and mostly associated with a history of head trauma. Only little is known about their natural development. They are characterized by an unpredictable course with a possibility of causing secondary intracranial hemorrhage with significant morbidity and mortality. We present two cases of traumatic pseudoaneurysms of the middle meningeal artery (MMA) treated via endovascular coil occlusion and review of literature. Pseudoaneurysms of the middle meningeal artery carry a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…[ 1 ] About 70–90% of traumatic MMA pseudoaneurysms are also associated with fracture across the MMA. [ 7 9 ] Tearing of the arterial wall by skull fracture or by separation of the dura mater and bone has been suggested. [ 14 ] When no risk factors were noted, it was suggested that pathophysiology is similar to that of the aneurysms of the Willis polygon.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] About 70–90% of traumatic MMA pseudoaneurysms are also associated with fracture across the MMA. [ 7 9 ] Tearing of the arterial wall by skull fracture or by separation of the dura mater and bone has been suggested. [ 14 ] When no risk factors were noted, it was suggested that pathophysiology is similar to that of the aneurysms of the Willis polygon.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports have described spontaneous resolution/thrombosis of MMA pseudoaneurysms[ 16 25 27 ] while others have ruptured several years after the suspected initial injury. [ 10 14 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic MMA pseudoaneurysms can be treated through surgical resection or by endovascular means. The most common treatment modality used is endovascular embolization with tissue adhesive or hydrogel agents,[ 3 9 11 14 18 ] followed by endovascular coiling[ 10 11 12 ] and surgical clipping or excision. [ 17 26 29 ] A large portion of patients undergoing embolization or surgery require a decompressive craniectomy for trauma-related hemorrhage, as seen in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The irrupture can cause various intracranial hemorrhages including epidural hematomas, 1) subdural hematomas, 2) and intracerebral hemorrhages. 3,4) For the most part, their etiology is associated with head trauma with skull fracture, while in non-traumatic cases, previous reports have demonstrated etiologies closely associated with primary diseases such as moyamoya disease, 5) neurofibromatosis, 6) meningioma, 7) cavernous hemangioma, 8) and ipsilateral cerebral vessel occlusion. 9) Postoperative middle meningeal artery aneurysms have not been reported with a clear angiographic appearance.…”
Section: Introductionmentioning
confidence: 99%